2010
DOI: 10.1088/0953-8984/22/32/323101
|View full text |Cite
|
Sign up to set email alerts
|

Protein stability and enzyme activity at extreme biological temperatures

Abstract: Psychrophilic microorganisms thrive in permanently cold environments, even at subzero temperatures. To maintain metabolic rates compatible with sustained life, they have improved the dynamics of their protein structures, thereby enabling appropriate molecular motions required for biological activity at low temperatures. As a consequence of this structural flexibility, psychrophilic proteins are unstable and heat-labile. In the upper range of biological temperatures, thermophiles and hyperthermophiles grow at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
268
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 270 publications
(279 citation statements)
references
References 85 publications
9
268
1
1
Order By: Relevance
“…In psychrophiles, this constraint is alleviated by the synthesis of cold-active enzymes to maintain metabolic fluxes compatible with life. The prevailing hypothesis assumes that cold-adapted enzymes have acquired a high catalytic activity at low temperature by improving their conformational flexibility at the expense of stability (7)(8)(9)(10). It has been shown that the crystal structure of psychrophilic enzymes is characterized by the disappearance of various noncovalent stabilizing interactions, resulting in both an improved dynamics of the enzyme conformation and in a weak stability (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…In psychrophiles, this constraint is alleviated by the synthesis of cold-active enzymes to maintain metabolic fluxes compatible with life. The prevailing hypothesis assumes that cold-adapted enzymes have acquired a high catalytic activity at low temperature by improving their conformational flexibility at the expense of stability (7)(8)(9)(10). It has been shown that the crystal structure of psychrophilic enzymes is characterized by the disappearance of various noncovalent stabilizing interactions, resulting in both an improved dynamics of the enzyme conformation and in a weak stability (11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…From top to bottom, mass scale from ~150 to ~15 kDa. The intense red fluorescence of the trigger factor (TF) spot correlates with its upregulation at 4°C, whereas the intense green fluorescence of the DnaK spot correlates with its down-regulation Adapted with permission from Piette et al, 2010. © 2010 In a typical single 2D-gel (Fig.…”
Section: Cold-induced Versus Cold-repressed Proteinsmentioning
confidence: 99%
“…Spot views on 2D-gels (circled) and three-dimensional images. Adapted with permission from Piette et al, 2010;Piette et al, 2011. © 2010Wiley and © 2011 American Society for Microbiology.…”
Section: Cold Shock and Heat Shock Proteinsmentioning
confidence: 99%
See 2 more Smart Citations